The action of the beta-agonist clenbuterol on protein metabolism in innervated and denervated phasic muscles. - Maltin, C A (1989)
1. Clenbuterol treatment in innervated and denervated phasic extensor digitorum longus, plantaris and gastrocnemius muscles from rats caused a significant increase in RNA and protein contents in all muscles except denervated extensor digitorum longus. 2. All muscles showed an increase in the fractional rate of protein synthesis (Ks) with clenbuterol, but the temporal response varied. 3. The data suggest that the effect of clenbuterol on protein metabolism in innervated muscles is muscle-type specific, and demonstrate the homology of response for denervated muscles.